Peran Camat di Era Otonomi Daerah - HAMUDY, MOH. ilHAM A. (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The Government of Indonesia has enacted Law No. 32 of 2004. It has affirmed that the head of a sub-district is a local apparatus of district/town, who acquires some of the government authorities from the district head/mayor. Such guarantee of partial authority is significant. With the authority in his hand, the sub- district head is able to set in motion and put in orders for the developments in his territory to be more dynamic, democratic, and legally-carried out. Nevertheless, the roles of the sub-district head—supposedly to mediate and overcome problems in society, as stated in the Law No. 5 of 1974—are no longer entirely accommodated in the Government Regulation No. 19 of 2008 issued by the central government to regulate sub-districts.